1994
DOI: 10.1068/p230129
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Content and Spatial Quantisation Effects in Face Recognition

Abstract: It has recently become apparent that if face images are degraded by spatial quantisation, or block averaging, there is a nonlinear acceleration of the decline in accuracy of recognition as block size increases. This suggests recognition requires a critical minimum range of object spatial frequencies. Two experiments were performed to clarify the phenomenon. In experiment 1, the speed and accuracy of recognition for six frontoparallel photographs of faces were measured. After familiarisation training sessions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
130
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(144 citation statements)
references
References 29 publications
14
130
0
Order By: Relevance
“…Hence, the information contained in a small medium range of SFs contributes more to the face-recognition process than the information contained in all the other SFs (Costen, Parker & Craw, 1994Näsänen, 1999;Parker & Costen, 1999). However, though all these results indicate that privileged information can be found in medium-range SFs, the role of the SFs outside that range cannot be overlooked.…”
Section: Theoretical Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Hence, the information contained in a small medium range of SFs contributes more to the face-recognition process than the information contained in all the other SFs (Costen, Parker & Craw, 1994Näsänen, 1999;Parker & Costen, 1999). However, though all these results indicate that privileged information can be found in medium-range SFs, the role of the SFs outside that range cannot be overlooked.…”
Section: Theoretical Discussionmentioning
confidence: 83%
“…The Masking Approach Initially, the main objective of research focusing on image filtering was the search for the range of SFs that are critical for face recognition. Although many results seem to indicate that middle-range SFs are the critical ones (Costen, Parker & Craw, 1994, it has been demonstrated that a large group of SFs, some of which are very far from the middle range, are needed to resolve recognition tasks with a good level of efficiency. Likewise, other results Face Perception 9 suggest that HSFs can also play an important role in face recognition (Fiorentini, Maffei & Sandini, 1983).…”
Section: Face Perceptionmentioning
confidence: 99%
See 1 more Smart Citation
“…In higher-level vision, numerous studies have examined how luminance cues supported the recognition of faces (Breitmeyer, 1984;Costen, Parker, & Craw, 1994;Fiorentini, Maffei, & Sandini, 1983;Sergent, 1986), objects (Parker et al, 1996), and scenes Parker, Lishman, & Hughes, 1992;Schyns & Oliva, 1994). It was found that fine-scale boundary edges (from high spatial frequencies) and coarser scale blobs (from low spatial frequencies) could selectively mediate different categorizations of the same stimuli (e.g., Schyns & Oliva, 1999).…”
Section: Luminance Color and Recognitionmentioning
confidence: 99%
“…Bachmann (1991), using a delayed match-to-sample task, found a rapid decrease in accuracy as coarse-quantized face images were reduced in resolution from 18 pixels per face width to 15. In related experiments, Costen et al (1994Costen et al ( , 1996, using a similar method to Bachmann's, found abrupt drop-offs in performance as faces were low-pass filtered at cutoffs less than 8 cycles per face or high-pass filtered at greater than 16 cycles per face. In experiments comparing human delayed match-to-sample performance with that of an ideal observer algorithm, Nasanen (1999) found a reduction in the efficiency function of participants when frequencies around 8 -13 cycles per face were masked by noise.…”
mentioning
confidence: 94%